(untitled) (Iranian Journal of Kidney Diseases, 2023)
Introduction. Despite many advances in the development of knowledge and application of new immunosuppressive medications over the past two decades, the improvement has only been seen in the short-term outcome of kidney transplantation while the long-term survival of kidney transplantation has not significantly improved. Allograft kidney biopsy may help to determine the causes of allograft dysfunction which may change the treatment strategy. Methods. In this retrospective study, kidney transplant recipients who underwent kidney biopsy in Shariati hospital during the years 2004 to 2015, at least three months after the kidney transplantation, were included for evaluation. Chi-square, ANOVA, post-hoc LSD, and T-test were used for data analysis. Results. A total number of 525 renal transplant biopsies were performed; 300 of them had complete medical records. The reported pathologies consisted of acute T-Cell mediated rejection (TCMR) (17%), interstitial fibrosis and tubular atrophy/chronic allograft nephropathy (IFTA/CAN) (15%), calcineurin inhibitor (CNI) nephrotoxicity (12.8%), borderline changes (10.3%), glomerulonephritis (GN) (8.9%), antibody mediated rejection (ABMR) (6.7%), transplant glomerulopathy (TG) (5.3%), normal (8.4%), and other pathologies (15.6%). C4d was positive in 19.9% of the biopsies. The pathology category had a significant correlation with allograft function (P < .001), but it had no significant relationship with age and gender of the recipient, donor and donor source (P > .05). Moreover, in about 50% of cases, treatment interventions were based on pathological results, which were effective in 77% of cases. The two-year graft and patient survival after kidney biopsy were 89% and 98%, respectively. Conclusion. Acute TCMR, IFTA/CAN, CNI nephrotoxicity were the most common causes of allograft dysfunction based on the transplanted kidney biopsy. In addition, pathologic reports were helpful for proper treatment. DOI: 10.52547/ijkd.7256